2020
DOI: 10.1039/c9dt03962g
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Sn- and Mg-doped hematite photoanodes for efficient photoelectrochemical water oxidation

Abstract: A feasible and cost-effective method was developed to improve the photoelectrochemical performance of hematite (α-Fe2O3) photoanode. Using a hydrothermal method, tin (Sn) and magnesium (Mg) (co-)doped hematite films were prepared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
4
24
1
Order By: Relevance
“…Doping with Zr 4+ , 5,6 Ti 4+ , 7 Sn 4+ , 8 Nb 5+ , 9 Ni 2+ , 10 and Mg 2+ , 11,12 is an approach to overcome the low electrical conductivity of hematite and improve its photocatalytic activities. Some of these observations demonstrated that the conductivity was improved due to the small polaron hopping mechanism, which leads to the enhancement of PEC properties 13–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping with Zr 4+ , 5,6 Ti 4+ , 7 Sn 4+ , 8 Nb 5+ , 9 Ni 2+ , 10 and Mg 2+ , 11,12 is an approach to overcome the low electrical conductivity of hematite and improve its photocatalytic activities. Some of these observations demonstrated that the conductivity was improved due to the small polaron hopping mechanism, which leads to the enhancement of PEC properties 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, its PEC application has been limited due to poor electrical conductivity, short charge carrier lifetime (<10 ps), and high recombination rate as a result of short hole diffusion length (2-4 nm). 4 Doping with Zr 4+ , 5,6 Ti 4+ , 7 Sn 4+ , 8 Nb 5+ , 9 Ni 2+ , 10 and Mg 2+ , 11,12 is an approach to overcome the low electrical conductivity of hematite and improve its photocatalytic activities. Some of these observations demonstrated that the conductivity was improved due to the small polaron hopping mechanism, which leads to the enhancement of PEC properties.…”
Section: Introductionmentioning
confidence: 99%
“…24 pristine α-Fe 2 O 3 photoanodes for PEC water oxidation, as indicated in Table S1, 28−36 including the highest IPCE (IPCE 420 ) of 36% at 420 nm for cauliflower α-Fe 2 O 3 prepared by the atmospheric pressure chemical vapor deposition (APCVD) technique. 32 Although α-Fe 2 O 3 -based photoanodes have been fabricated via various physical and chemical techniques such as chemical vapor deposition, 37−39 ultrasonic spray pyrolysis, 40 atomic layer deposition, 41 dense solutionbased regrown, 42 e-beam evaporation, 43 electrodeposition, 44 and hydrothermal, 36 a facile way available for mass production of α-Fe 2 O 3 photoanodes is mandatory for practical systems of solar-driven water splitting. Recently we found that the presence of 1-methylimidazole in precursor methanolic solutions (or suspensions) containing metal ions leads to rigidly adhered films of the corresponding metal oxides on various electrode substrates upon sintering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A few reports are available in the literature on the study of photoconversion and water-splitting efficiency of Mg-doped iron oxide as adsorbents of various chemicals. [8][9][10] A study undertaken by Ingler et al [8] using Mg-doped iron (III) oxide thin films prepared by spray pyrolysis reported a maximum photoconversion efficiency of 0.33%. A hydrothermal method was utilized by Cai et al [9] to prepare tin and magnesium co-doped hematite films as photoanode for water splitting that attained a maximum photocurrent density of 1.1 mA cm À2 , which was better than the pristine α-Fe 2 O 3 by three times.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A study undertaken by Ingler et al [8] using Mg-doped iron (III) oxide thin films prepared by spray pyrolysis reported a maximum photoconversion efficiency of 0.33%. A hydrothermal method was utilized by Cai et al [9] to prepare tin and magnesium co-doped hematite films as photoanode for water splitting that attained a maximum photocurrent density of 1.1 mA cm À2 , which was better than the pristine α-Fe 2 O 3 by three times. The improvement in its performance was ascribed to the increase in charge injection efficiency and charge separation efficiency due to Mg doping.…”
Section: Introductionmentioning
confidence: 99%